Comparison of proteinuria diagnostic methods in pregnant patients - Özge Özdemir; Gökhan Bolluk; Ulaş Çoban (Perinatal Medicine Foundation, 2023)
Objective: This study aimed to compare spot urine protein-to-creatinine ratio and 24-hour urine methods in pregnant patients and to evaluate the accuracy of spot urine protein-to-creatinine ratio against the reference standard 24-hour urine method. Methods: This retrospective study included 399 pregnant patients diagnosed with proteinuria, gestational hypertension, or preeclampsia. Urinary protein concentrations were measured by spot dipstick urine analysis, spot urinary protein-to-creatinine, and 24-hour total proteinuria via 24-hour urine collection. The 24-hour total proteinuria measurement was accepted as the reference standard for diagnosis of proteinuria, and significant proteinuria was defined ≥300 mg of protein in the 24-hour urine collection. Results: According to the receiver operating characteristics analysis of the spot urinary protein-to-creatinine ratio measurements, the cut-off value of the protein-to-creatinine ratio method was ≥0.443 mg protein/mg creatinine, the area under the curve was 0.887, the sensitivity was 77.14%, the specificity was 87.76%, and the accuracy was 84.96%. According to the receiver operating characteristics analysis of the 24-hour total proteinuria measurements, these values were >0.405 mg/day, 0.874, 82.86%, 84.64%, and 84.17%, respectively. No difference was observed between these two proteinuria methods regarding the receiver operating characteristics analysis (p=0.475). There was a strong and significant correlation between the spot urine protein-to-creatinine ratio and the 24-hour total proteinuria (r=0.842, p<0.001). Conclusion: Our findings revealed that there was a strong and significant correlation between the spot urine protein-to-creatinine ratio and the 24-hour total proteinuria, and it may be used as an alternative to the 24-hour total proteinuria. In addition, the spot urine protein-to-creatinine ratio is noteworthy, especially in an emergency situation in pregnant women for whom the time is limited to make a rapid clinical decision.